Microbiota thrombus colonization may influence athero-thrombosis in hyperglycemic patients with ST segment elevation myocardialinfarction (STEMI). Marianella study. (March 2021) - Sardu, Celestino; Consiglia Trotta, Maria; Santella, Biagio; D'Onofrio, Nunzia; Barbieri, Michelangela; Rizzo, Maria Rosaria; Sasso, Ferdinando Carlo; Scisciola, Lucia; Turriziani, Fabrizio; Torella, Michele; Portoghese, Michele; Loreni, Francesco; et al.
Abstract: Objectives: We examined the association of the coronary thrombus microbiota and relative metabolites with major adverse cardiovascular events (MACE) in hyperglycemic patients with ST segment elevation myocardial infarction (STEMI). Background: Hyperglycemia during STEMI may affect both development and progression of coronary thrombus via gut and thrombus microbiota modifications. Methods: We undertook an observational cohort study of 146 first STEMI patients treated with primary percutaneous coronary intervention (PPCI) and thrombus-aspiration (TA). Patients were clustered, based on admission blood glucose levels, in hyperglycemic (≥140 mg/dl) and normoglycemic (<140 mg/dl). We analyzed gut and thrombus microbiota in all patients. Moreover, we assessed TMAO, CD40L and von Willebrand Factor (vWF) in coronary thrombi. Cox regressions were used for the association between Prevotella spp. and TMAO terziles and MACE. MACE endpoint at 1 year included death, re-infarction, unstable angina. Results: In fecal and thrombus samples, we observed a significantly different prevalence of both Prevotella spp. and Alistipes spp. between patients with hyperglycemia (n = 56) and those with normal glucose levels (n = 90). The abundance of Prevotella increased in hyperglycemic vs normoglycemic patients whereas the contrary was observed for Alistipes . Interestingly, in coronary thrombus, the content of Prevotella was associated with admission blood glucose levels (p < 0.01), thrombus dimensions (p < 0.01), TMAO, CDL40 (p < 0.01) and vWF (p < 0.01) coronary thrombus contents. Multivariate Cox-analysis disclosed a reduced survival in patients with high levels of Prevotella and TMAO in coronary thrombus as compared to patients with low levels of Prevotella and TMAO, after 1-year follow up. Conclusions: Hyperglycemia during STEMI may increase coronary thrombus burden via gut and thrombus microbiota dysbiosis characterized by an increase of Prevotella and TMAO content in thrombi. Clinical Trial Registration : NCT03439592. September 30, 2016. Ethic Committee Vanvitelli University: 268/2016.